Retinoic acid receptor beta protects striatopallidal medium spiny neurons from mitochondrial dysfunction and neurodegeneration. (May 2022) - Ciancia, Marion; Rataj-Baniowska, Monika; Zinter, Nicolas; Baldassarro, Vito Antonio; Fraulob, Valérie; Charles, Anne-Laure; Alvarez, Rosana; Muramatsu, Shin-ichi; de Lera, Angel R.; Geny, Bernard; Dollé, Pascal; Niewiadomska-Cimicka, Anna; et al.
Abstract: Retinoic acid is a powerful regulator of brain development, however its postnatal functions only start to be elucidated. We show that retinoic acid receptor beta (RARβ), is involved in neuroprotection of striatopallidal medium spiny neurons (spMSNs), the cell type affected in different neuropsychiatric disorders and particularly prone to degenerate in Huntington disease (HD). Accordingly, the number of spMSNs was reduced in the striatum of adult Rarβ -/- mice, which may result from mitochondrial dysfunction and neurodegeneration. Mitochondria morphology was abnormal in mutant mice whereas in cultured striatal Rarβ -/- neurons mitochondria displayed exacerbated depolarization, and fragmentation followed by cell death in response to glutamate or thapsigargin-induced calcium increase. In vivo, Rarβ -/- spMSNs were also more vulnerable to the mitochondrial toxin 3-nitropropionic acid (3NP), known to induce HD symptoms in human and rodents. In contrary, an RARβ agonist, AC261066, decreased glutamate-induced toxicity in primary striatal neurons in vitro, and diminished mitochondrial dysfunction, spMSN cell death and motor deficits induced in wild type mice by 3NP. We demonstrate that the striatopallidal pathway is compromised in Rarβ -/- mice and associated with HD-like motor abnormalities. Importantly, similar motor abnormalities and selective reduction of spMSNs were induced by striatal or spMSN-specific inactivation of RARβ, further supporting a neuroprotective role of RARβ in postnatal striatum. Highlights: RARβ selectively protects Drd2 + striatopallidal medium spiny neurons (spMSNs) from degeneration in adult mouse brain. Loss of RARβ leads to mitochondrial dysfunction and increased vulnerability of MSNs to cell death in Rarβ -/- mice. RARβ agonist prevents mitochondrial failure and loss of Drd2 + spMSNs induced by mitochondrial toxin 3-NP in mice.